Efficient artificial light-harvesting systems with gel properties formed by ion recognition. Issue 11 (18th May 2022) - Ma, Xinxian; Qiao, Bo; Yue, Jinlong; Geng, Yutao; Lai, Yingshan; Zhang, Jiali; Feng, Enke; Li, Zhenliang; Han, Xingning
Abstract : A novel supramolecular gelator (G3) exhibited excellent selectivity toward Mg 2+ as well as showed excellent gelation abilities. Meanwhile, an efficient artificial light-harvesting system has been constructed between G3@Mg-sol or G3@Mg-gel and RhB. Abstract : We constructed a novel supramolecular gelator (G3) by using acylhydrazone, which exhibited excellent selectivity and ultrasensitive sensing properties toward Mg 2+ in ethanol as well as showed excellent gelation abilities in glycol–H2 O. Meanwhile, an efficient artificial light-harvesting system (ALHS) has been successfully constructed between G3@Mg-sol or G3@Mg-gel and a hydrophobic fluorescent dye (RhB).